Design of Individual Learning Trajectory Based on Mixed Diagnostic Tests and Cognitive Graphic Tools; Modelling, Identification and Control. Parallel and Distributed Computing and Networks. Software Engineering - Yankovskaya A. E. Anna Efimovna; Dementiev Yu. N. Yuriy Nikolaevich; Lyapunov D. Yu. Danil Yurievich; Yamshanov A. Artem (2016, 2016)
Title screen